PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DAN MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - KURNIA PUTRI, RAHMANITA (Jurnal Akuntansi AKUNESA, 2018)
This research examinesw whether of sustainability report and corporate governance mechanism toward company profitability. This study used secondary data in the from of annual reports and financial statements food and beverage companies listed on the BEI periode 2013 ? 2015. The result showed that simultaneously economy disclouse, environmental performance disclouser,labor practice an decent work, society disclouse, product responsibility disclouse, independent board and board of directors have significant effect on ROA, while current ratio do not affect simultaneously. Pertially, by economy disclouse, society disclouse and independent board has a significant effect on ROA. While environmental performance disclouser,labor practice an decent work, product responsibility disclouse and board of directors but not significant on ROA